STRATEGI METODE LAFDZI DALAM MEMBIMBING HAFALAN SURAT-SURAT PENDEK JUZ 30 PADA ANAK KELOMPOK B DI RA NURUL QUR’AN - Wildan, Arifatul; Aziz Wahab, Abdul; Hafidlatil Kiromi, Ivonne (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation strategy of the Lafdzi method in guiding the memorization of short surahs of Juz 30 for Group B children at RA Nurul Qur’an. The research employed a descriptive qualitative approach using participatory observation, semi-structured interviews, and documentation techniques. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the Lafdzi method, implemented through listening, collective repetition, individual repetition, and daily habituation, accelerates the memorization process. Before the implementation of the method, children required approximately 4–5 days to memorize one short surah. After consistent implementation, the memorization period decreased to 2–3 days per surah. In addition, improvements were observed in pronunciation fluency, reduction of recitation errors, and increased self-confidence during memorization submission. These findings suggest that the Lafdzi method is effective for early childhood Qur’anic memorization learning as it aligns with children’s language and memory development characteristics.